Palaeoenvironment evolution and organic matter enrichment mechanisms of the Wufeng-Longmaxi shales of Yuanán block in western Hubei, middle Yangtze: Implications for shale gas accumulation potential. (June 2023) - Xu, Lulu; Huang, Saipeng; Wang, Yang; Zhou, Xianghui; Liu, Zaoxue; Wen, Yaru; Zhang, Yanlin; Sun, Mengdi
Abstract: The deposition of black shale is influenced by several factors, including organic matter input, which is controlled by primary productivity; preservation, which is governed by redox conditions and deposition rates; and dilution, which is controlled by terrigenous input. However, determining the individual contribution of these factors to organic matter enrichment (OME) is complex due to significant variations in palaeodepositional conditions across different regions. In this study, we aimed to investigate the palaeoenvironmental conditions and OME mechanisms in the Wufeng-Longmaxi Formation in western Hubei by integrating data on total organic carbon (TOC) content, mineral compositions, and major and trace elements. We also examined the rapid variations in the palaeoenvironment, which led to the mass extinction in the Late Ordovician. Our findings indicate that dolomite siltstone and silty dolomite are present in the Guanyinqiao Formation (GYQ), which differs from other regions. The silica in the Wufeng-Longmaxi Formation has a mainly nonhydrothermal origin, while the upper Wufeng Formation (WF) has an entirely biogenic source. The organic-rich shales were primarily deposited in a warm and humid climate with low terrigenous input, low salinity, dysoxic conditions, and moderate to high palaeoproductivity due to moderate to strong upwelling. The GYQ serves as a transitional section from the WF to the Longmaxi Formation, which was characterized by a cold climate, oxic conditions, weak upwelling, and deposition in a strongly restricted setting, potentially leading to the mass extinction. Overall, OME was primarily dominated by preservation, with factors that influenced OME changing vertically. Palaeoproductivity, combined palaeoproductivity and palaeoredox conditions, and palaeoredox conditions were the main controlling factors in the WF, the Lower Longmaxi Formation (LLMX), and the Upper Longmaxi Formation (ULMX), respectively. Additionally, the Huangling basement, a submarine high, and the Xuefeng uplift's uplift and compression played important roles in OME. However, shale gas exploration prospects in the study area are limited due to the thinness of the organic-rich shales, oxic to dysoxic conditions, and relatively low palaeoproductivity. Highlights: Guanyinqiao Formation exhibits unique characteristics in terms of dolomite siltstone and silty dolomite formation. Organic matter enrichment in the study area is primarily influenced by preservation conditions. Shale gas accumulation potential in Huangling submarine high is limited.